Shaping Christianity in Calagurris: Prudentius's renouatio of Ambrose in Peristephanon 1 - Kirsch, Kathleen (Journal of early Christian studies, 2024)
At the close of the fourth century, the ideal shape of Christianity was hotly contested. The veneration of saints and their relics, the significance of celibacy and asceticism, the nature of Christ, and many other aspects of faith and spirituality were disputed. A profusion of literary works, extant and not, explicitly addressed the intricate web of debated topics; Prudentius’s Peristephanon 1, however, has been understood in isolation from this cultural and ideological contest. This article identifies Ambrose’s Hymn. 10 as a significant source for Peri. 1; the former provided Prudentius with a framework upon which he built a narrative of martial martyrdom and of saintly identity for the unstoried relics in his hometown of Calagurris. Peri. 1 repurposes Hymn. 10’s vocabulary, concepts, classical allusions, and a dynamic of envy (inuidia) directed by the historical persecutor against the contemporary audience. The purpose of the poet’s renouatio, however, is more than hagiographical expansion; Prudentius replicates Ambrosian tropes to define his local Christian community in relation to its patronal martyrs. Peri. 8 builds on the foundation of Peri. 1, portraying the martyrs of Calagurris as not only patrons but also imitable models for the city’s residents. Emeterius and Chelidonius become the exemplars of both historical and contemporary Calagurran Christianity. Thus, Prudentius uses an Ambrosian exemplar to provide a localized response to the discourse of the day, deliberated throughout the empire.